Disinformation tackling in the metaverse and the Digital Services Act - Tanel Kerikmäe; Ondrej Hamuľák; Matúš Mesarčík (Cogent Social Sciences)
The emergent metaverse presents novel challenges for online information integrity. Disinformation in immersive environments can be particularly pernicious, blurring the lines between reality and fiction. This study explores the multifaceted phenomenon of disinformation in metaverse, examining its potential forms, methods of propagation and the unique risks it poses. We then delve into the regulatory landscape, specifically analysing the EU’s Digital Services Act (DSA) as a potential framework to combat disinformation in this new virtual frontier. In doing so, the study assesses the strengths and limitations of the DSA in addressing the complexities of metaverse disinformation. Through critical analysis, we explore how the DSA’s specific scope and provisions on content removal, platform accountability and transparency can be adapted to the metaverse context.